2019
DOI: 10.1021/acsami.9b05384
|View full text |Cite
|
Sign up to set email alerts
|

Study of in Situ Silver Migration in Amorphous Boron Nitride CBRAM Device

Abstract: We report the dependence of the thickness of amorphous boron nitride (a-BN) on the characteristics of conductive bridge random access memory (CBRAM) structured with the Ag/a-BN/Pt stacking sequence. The a-BN thin film layers of three different thicknesses of 5.5, 11, and 21.5 nm were prepared by the sputtering deposition. Depending on the thickness of the a-BN layer, the devices are found to be in either low-resistance state (LRS) or high-resistance state (HRS) prior to any consecutive switching cycle. All dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 40 publications
(56 reference statements)
1
43
0
1
Order By: Relevance
“…The most deposition techniques were prepared by DC reactive sputtering or RF sputtering for good resistive switching. Ag electrode tends to smaller operation voltage compared to the Cu electrode due to high diffusivity [ 21 , 26 , 43 , 44 , 45 ]. The selector and synaptic device applications are demonstrated even though the resistive switching performances of Cu/AlN/TiN in this work are not overwhelming compared to the previous works.…”
Section: Resultsmentioning
confidence: 99%
“…The most deposition techniques were prepared by DC reactive sputtering or RF sputtering for good resistive switching. Ag electrode tends to smaller operation voltage compared to the Cu electrode due to high diffusivity [ 21 , 26 , 43 , 44 , 45 ]. The selector and synaptic device applications are demonstrated even though the resistive switching performances of Cu/AlN/TiN in this work are not overwhelming compared to the previous works.…”
Section: Resultsmentioning
confidence: 99%
“…The in situ Ag + ions migration during the Ag thin‐film deposition leading to the Ag filament formation in amorphous BN (a‐BN) thin film was confirmed in a previous study. [ 35 ] Moreover, a number of studies have been conducted which confirmed the formation of conducting filaments as well as electrochemically active metal ions migration in various switching materials including h ‐BN. [ 6,13,27,36 ]…”
Section: Figurementioning
confidence: 99%
“…[ 42,43 ] There have been noteworthy endeavors toward understanding the operating mechanism of resistive switching (RS) of the vertical stacked memristors. [ 44–52 ] Boron ionic migration and conductive filament formation have been used to control spatially electrical conductivity in BN memristors, studied by a bunch of characteristic methods, such as transmission electron microscope (TEM), [ 53–55 ] conductive atomic force microscope (CAFM), [ 56,57 ] electron energy loss spectroscopy (EELS), [ 54,57 ] and I – V electrical measurement. [ 33,34,53,54,56–58 ] Interestingly, it is reported that nonvolatile and volatile resistive switching transition can be modulated in BN by altering test parameters (SET and RESET voltage ranges, compliance currents, etc.…”
Section: Introductionmentioning
confidence: 99%